Does green accounting influences ecological sustainability? Evidence from a developing economy - Ishmael Wiredu; Andrew Osei Agyemang; Samuel Yayra Agbadzidah (Cogent Business & Management, 2023)
This study examined the impact of green accounting on ecological sustainability and employed environmental costs as a mediation between green accounting and sustainability. The study focused on pharmaceutical companies because of the heavy use of natural resources and the subsequent greenhouse gases and wastewater from this sector pose a risk to the ecological system. The data utilized in this research was obtained from 372 respondents from 35 registered members of Pharmaceutical Manufacturers Association of Ghana through online questionnaire. PLS-SEM was used to analyze the data and tested the hypotheses for the study using SMART-PLS 4. The findings revealed that environmental compliance and business efficiency have a major and constructive effect on sustainability, and also discovered that environmental costs mediated the impact of green accounting on sustainability. This study recommends that policymakers and corporations must take a holistic and coordinated approach when considering the effects of their actions on society and the environment.
Keywords: 650; Ghana; green accounting; pharmaceutical firm; PLS-SEM; sustainability